2021
DOI: 10.3233/jad-201055
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss Induces Memory Impairment and Gliosis in App Knock-In Mouse Models of Alzheimer’s Disease

Abstract: Background: Epidemiological studies have shown that tooth loss is associated with Alzheimer’s disease (AD) and dementia. However, the molecular and cellular mechanisms by which tooth loss causes AD remain unclear. Objective: We investigated the effects of tooth loss on memory impairment and AD pathogenesis in App NL - G - F mice. Methods: Maxillary molar teeth on both sides were extracted from 2-month-old AppNL - G - F mice, and the mice were reared for 2 months. The short- and long-term memory functions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 65 publications
3
21
0
Order By: Relevance
“…Tooth loss induces the activation of inflammatory cells. Taslima et al ( 2021 ) reported that, after tooth extraction in mice with amyloid precursor protein ( App ) gene knock-in (a mouse model of AD), the numbers of microglia and astrocytes in the hippocampus increased, and a large number of inflammatory cytokines (such as tumor necrosis factor alpha [TNF-α], interleukin-1 [IL-1], and IL-6) were produced, thereby promoting an inflammatory state in neurons in the hippocampus and prefrontal cortex. Early tooth loss can also lead to malnutrition and chronic stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tooth loss induces the activation of inflammatory cells. Taslima et al ( 2021 ) reported that, after tooth extraction in mice with amyloid precursor protein ( App ) gene knock-in (a mouse model of AD), the numbers of microglia and astrocytes in the hippocampus increased, and a large number of inflammatory cytokines (such as tumor necrosis factor alpha [TNF-α], interleukin-1 [IL-1], and IL-6) were produced, thereby promoting an inflammatory state in neurons in the hippocampus and prefrontal cortex. Early tooth loss can also lead to malnutrition and chronic stress.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic stress is closely related to inflammation. After teeth extraction, chronic stress activates glial cells and release excess ROS, causing an inflammatory cascade effect in the central nervous system (Taslima et al, 2021 ). Chronic inflammation will also interact with chronic stress and oxidative stress, thereby aggravating nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is widely accepted that periodontitis is involved in the synthesis and accumulation of amyloid β, which is a pathologic hallmark of the AD brain [28]. Regardless of amyloid cascade, one experimental study demonstrated that tooth loss induces memory impairment through decreased neuronal activity and glial activation in an AD model [10]. Additionally, it has been suggested that the decreased mastication induced by tooth loss reduces orofacial sensorimotor activity, which eventually inhibits hippocampal neurogenesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss is a prevalent condition in the elderly population, representing a problem for general health and consequently negatively impacting quality of daily life and cognitive function. Clinical studies have indicated that tooth loss is associated with AD and dementia [5][6][7][8], and experimental studies have demonstrated that tooth loss leads to memory deterioration and loss of neuronal cells [9][10][11]. Although the exact mechanism that links tooth loss with decreased cognitive function has not been determined, some investigators have proposed that tooth loss induces masticatory abnormalities, nutritional changes, and hippocampal damage [12].…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of CO 2 was used to kill the mice, which were then perfused with 0.1 M PBS. The brains of all mouse samples were removed and the cortical tissues of the left hemisphere were snap-frozen in liquid nitrogen and stored at − 80 °C until biochemical analysis, as described previously 49 . The cortical tissues were homogenized in 19 volumes of Tris-buffered saline (TBS; pH 7.6, 10 mM Tris and 150 mM NaCl) containing a phosphatase inhibitor cocktail (Wako Pure Chemical Industries, Osaka, Japan) and a protease inhibitor cocktail (Roche, Mannheim, Germany) and centrifuged at 100,000 rpm for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%